The role of exogenous histamine in atopic dermatitis flare-ups - Kowalska, Zofia; Narbutt, Joanna (Alergologia Polska - Polish Journal of Allergology, 2024)
Atopic dermatitis (AD) remains a significant challenge due to its chronic and relapsing nature, with various triggers exacerbating symptoms. While endogenous histamine’s role in AD is well documented, the impact of exogenous histamine remains controversial. This review explores the complex relationship between exogenous histamine and AD flare-ups, evaluating evidence for implementing low-histamine diets and diamine oxidase enzyme supplementation as a potential therapeutic intervention in a subgroup of AD patients. Histamine’s diverse physiological functions, its involvement in AD pathophysiology, and the potential implications of histamine intolerance and histamine overlay syndrome are examined. Studies suggest compromised metabolism and increased sensitivity to dietary histamine, highlighting the potential of low-histamine diets in managing symptoms. Despite limited research, preliminary findings underscore the need for further exploration of histamine-related reactions in AD and the therapeutic potential of low-histamine diets. Future research avenues include developing reliable screening tools and elucidating the relationships between gut microbiome dysbiosis and histamine metabolism in AD.